Association between IFN-γ +874A/T and IFN-γR1 (-611A/G, +189T/G, and +95C/T) Gene Polymorphisms and Chronic Periodontitis in a Sample of Iranian Population - Zahra Heidari; Hamidreza Mahmoudzadeh-Sagheb; Mohammad Hashemi; Somayeh Ansarimoghaddam; Bita Moudi; Nadia Sheibak (International Journal of Dentistry)
Background. Interferon gamma (IFN-γ) is an immune regulatory cytokine that acts through its receptor and plays important role in progression of inflammatory disease such as chronic periodontitis (CP). The purpose of this study was to determine the differences in the distribution of IFN-γ (+874A/T) and IFN-γR1 (-611A/G, +189T/G, and +95C/T) gene polymorphisms among CP and healthy individuals and to investigate relationships between these polymorphisms and susceptibility to CP. Materials and Methods. 310 individuals were enrolled in the study including 210 CP patients and 100 healthy controls. Single nucleotide polymorphisms at IFN-γ (+874A/T) and IFN-γR1 (-611A/G, +189T/G, and +95C/T) were analyzed by ARMS-PCR and PCR-RFLP methods. Results. The significant difference was found in genotype and allele frequency of IFN-γ (+874A/T) gene polymorphism in chronic periodontitis patients and healthy controls. The distribution of genotypes and allele frequencies for IFN-γR1 (-611A/G, +189T/G, and +95C/T) were similar among the groups and no differences in the frequencies of alleles or genotypes of IFN-γR1 genetic polymorphisms variants between case and control groups were detected. Conclusion. The finding of this study showed that IFN-γ +874A/T gene polymorphism may affect susceptibility to CP, whereas IFN-γR1 genetic polymorphisms at -611A/G, +189T/G, and +95C/T were not associated with this disease.